Double exponentially weighted moving average control chart with supplementary runs-rules. Issue 2 (3rd March 2020) - Adeoti, Olatunde A.; Malela-Majika, Jean-Claude
ABSTRACT: Enhancing the sensitivity of control charts for detecting small process shift is desirable and may be done in different ways. In this paper, we propose the double exponentially weighted moving average (DEWMA) control chart using the 2- of -2 and 1- of -1 or 2- of -2 runs-rules schemes for monitoring process mean shifts. The performances of the resulting control schemes are investigated in terms of the average run-length ( A R L ), standard deviation of the run-length ( S D R L ) and selective percentiles of the run-length ( P R L ). In addition, the overall performance of the proposed runs-rules charts are examined and compared with those of the existing charts in terms of the A R L, average extra quadratic loss ( A E Q L ), average ratio of the average run-length ( A R A R L ) and performance comparison index ( P C I ) values. It is observed that the proposed control schemes are more efficient in many situations and improve the ability of the existing DEWMA schemes in detecting small, moderate and large mean shifts.